Information Security: Design, Implementation, Measurement, and Compliance - Layton, Timothy (CRC Press, 2009)
Organizations rely on digital information today more than ever before. Unfortunately, that information is equally sought after by criminals. New security standards and regulations are being implemented to deal with these threats, but they are very broad and organizations require focused guidance to adapt the guidelines to their specific needs.